DEVELOPING AN INTEGRATIVE LEADERSHIP CAPACITY MODEL IN EDUCATION: A SYSTEMATIC SYNTHESIS OF EMPIRICAL EVIDENCE AND STRATEGIC IMPLICATIONS FOR INDONESIA - Wulandari, Dea Ayu; Vivianita, Rahma; Mahdum, Mahdum; Dahnilsyah, Dahnilsyah; Azhar, Fadly (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Objective: This study aims to bridge this gap by systematically synthesizing empirical findings from a diverse set of studies to construct a comprehensive and integrative model for building educational leadership capacity. Methods: Employing a systematic literature synthesis approach, this research critically analyzed 10 empirical studies (3 from Indonesian national journals, 7 from international publications) using a comparative thematic analysis framework to identify core constructs, effective practices, and contextual variables. Results: The synthesis culminated in the development of an integrative model composed of four interconnected pillars: (1) Foundational Values and Ethical Character, (2) Collaborative and Relational Competencies, (3) Enabling Organizational Systems and Structures, and (4) Continuous, Job-Embedded Learning Processes. The model positions leadership as a dynamic, developmental capacity that is cultivated at the intersection of individual growth and systemic support. Implications: The proposed model provides an actionable framework for policymakers, educational leaders, and teacher training institutions in Indonesia to design targeted leadership development initiatives, revise existing policies, and foster a sustainable culture of collective leadership.